Effect of Different Types of Construction Techniques on the Vertical Fit of Screw-Retained Fixed Implant-Supported Prosthesis - Mohammad Reza Nakhaee; Azizollah Moraditalab; Taraneh Zeinalzadeh ghochani; Davood Nodehi (Mashhad University of Medical Sciences, 2021)
Introduction: Marginal misfit in screw-retained implant restorations when screwing torque leads to deformation of superstructure and formation of strain in the lower bone. Therefore, decreasing the marginal gap is considered one of the therapeutic goals in the fabrication of screw-retained implant-supported prostheses. This study aimed to investigate the effect of four framework construction techniques on the marginal accuracy of screw-retained implant-supported fixed partial restorations. Materials and Methods: The main model was an acrylic block with two implants that simulated 3-unit implant-supported screw-retained prostheses with a second premolar pontic. Standard abutments for screw veneers on implants were tightened with 25 Ncm torque. In this study, six metal frameworks were fabricated using four techniques, namely integrated casting, soldering, double casting, and soft metal CAD/CAM cobalt-chrome on the abutments and the marginal gap in the anterior and posterior bases was evaluated by the standard one screw test method. In the next step, the occlusal screw of both pins was tightened and the marginal gap was re-measured (definite fit). The mean scores of marginal gap values ​​were calculated in terms of passive fit and definitive fit. Finally, the results were assessed using one-way ANOVA and Tamhane post-hoc tests (p < 0.05). Results: The mean scores of the marginal gap were significantly different among the four studied groups regarding both passive fit and definitive fit (p < 0.001). According to the Tamhane post hoc test in the passive fit condition, the mean scores of marginal gap of CAD/CAM group were significantly lower than those in the other groups (p < 0.001). Conclusion: The passivity of the screw-retained fixed implant frameworks was influenced by the manufacturing technique. It was revealed that CAD/CAM method exhibited the best passivity, compared to three conventional studied methods.